The Bully-Victim Overlap and Vaping Activity Among Adolescents. (July 2023) - Boccio, Cashen M.; Leal, Wanda E.
Previous research links substance use with bullying perpetration and bullying victimization. Limited research, however, has explored how vaping, is related to bullying activities. What limited research has been conducted links vaping with bullying victimization in some samples. However, the relationship between vaping and the victim-offender overlap is extremely limited. This study addresses this gap in the literature by exploring the associations between nicotine and marijuana vaping and bullying perpetration and victimization both in-person and online. In addition, we explore the relationship between vaping and holding bully-victim status. Our results suggest that marijuana vaping is associated with in-person bullying and nicotine vaping is associated with many facets of both in-person and cyber bullying experiences.